2018
DOI: 10.1080/0886022x.2018.1537930
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the diagnosis of glomerular diseases in east China: a 15-year renal biopsy study

Abstract: Background: There have been some gradual changes in the distribution of renal biopsy pathological diagnoses during recent years. This study aimed to show changes in renal disease prevalence in China by investigating 10 patients diagnosed at our Kidney Disease Centre during the last 15 years.Methods and results: All patients aged 15-year-old or older who underwent renal biopsy at the First Affiliated Hospital, Zhejiang University, from 2001 to 2015 were enrolled. There were 5 common types of primary glomerulone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
25
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 34 publications
(35 reference statements)
11
25
2
Order By: Relevance
“…Present evidences suggested that MN had the largest proportion of morbidity in elderly patients, while MCD accounts for the highest proportion of primary nephrotic syndrome in young patients [3,19,20]. Our experiments reached similar results that the age at biopsy had a certain in uence on the nomogram.…”
Section: Discussionsupporting
confidence: 85%
“…Present evidences suggested that MN had the largest proportion of morbidity in elderly patients, while MCD accounts for the highest proportion of primary nephrotic syndrome in young patients [3,19,20]. Our experiments reached similar results that the age at biopsy had a certain in uence on the nomogram.…”
Section: Discussionsupporting
confidence: 85%
“…In this context, the crucial TCM concept for treating PNS is to invigorate Qi, activate blood, and remove stasis, which might increase the rationality and applicability of our results. Idiopathic membranous nephropathy, which, besides IgA nephropathy, is a prevalent pathological type of PNS in China [23], has been shown to positively respond to the Qi-invigorating and stasis-removing method; moreover, the most frequently used Chinese medicines have been reported to be Astragali Radix, Angelicae Sinensis Radix, Chuanxiong Rhizoma, and Salvia Miltiorrhiza [24].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, readers should keep these things in mind when they compare the results of studies. Table 1 summarizes the previous publications on frequencies of biopsy-proven renal diseases reported in China, Japan, and South Korea [1][2][3][4][5][6][7][8][9]. These data show major biopsy-proven glomerular diseases in East Asian countries.…”
mentioning
confidence: 87%
“…According to the underlying etiology, MsPGN could be further classified as immunoglobulin A (IgA) nephropathy, lupus nephritis, C3 glomerulopathy, and so on. Therefore, analyses using the term MsPGN in previous studies [1,2] cannot be directly compared to other reports using refined terminologies. Secondly, indications for performing renal biopsy in patients suspected of kidney disease are quite different among countries, institutions, and even clinicians.…”
mentioning
confidence: 99%